Last visit was: 16 Jul 2024, 12:11 It is currently 16 Jul 2024, 12:11
Toolkit
GMAT Club Daily Prep
Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History
Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.
Request Expert Reply

# If x = -1, then -(x^4 + x^3 + x^2 + x) =

SORT BY:
Tags:
Show Tags
Hide Tags
Math Expert
Joined: 02 Sep 2009
Posts: 94370
Own Kudos [?]: 641393 [0]
Given Kudos: 85332
Math Expert
Joined: 02 Sep 2009
Posts: 94370
Own Kudos [?]: 641393 [0]
Given Kudos: 85332
Intern
Joined: 30 Jan 2014
Posts: 13
Own Kudos [?]: 160 [1]
Given Kudos: 4
Intern
Joined: 01 Apr 2012
Status:FTW
Posts: 8
Own Kudos [?]: 22 [1]
Given Kudos: 260
Location: India
Concentration: International Business, Leadership
GMAT Date: 09-27-2014
GPA: 3.5
WE:Consulting (Venture Capital)
Re: If x = -1, then -(x^4 + x^3 + x^2 + x) = [#permalink]
1
Kudos
-[(-1)^4 + (-1)^3 +(-1)^2 +(-1)^1] = (1-1+1-1) = 0
Is (C) that answer?
Manager
Joined: 20 Dec 2013
Posts: 183
Own Kudos [?]: 291 [1]
Given Kudos: 35
Location: India
Re: If x = -1, then -(x^4 + x^3 + x^2 + x) = [#permalink]
1
Kudos
Ans should be '0' but it's not in the options.

Any -ve raised to even power will be +ve
Any -ve raised to odd power will remain -ve.

And '1' raised to any power=1 only.
Therefore, the question becomes -(1-1+1-1)=0
Math Expert
Joined: 02 Sep 2009
Posts: 94370
Own Kudos [?]: 641393 [0]
Given Kudos: 85332
Re: If x = -1, then -(x^4 + x^3 + x^2 + x) = [#permalink]
Expert Reply
SOLUTION

If x = -1, then -(x^4 + x^3 + x^2 + x) =

(A) -10
(B) - 4
(C) 0
(D) 4
(E) 10

Substitute x = -1:

$$-(x^4 + x^3 + x^2 + x) =-(1-1+1-1)=0$$.

Answer: C.
GMAT Club Legend
Joined: 03 Jun 2019
Posts: 5291
Own Kudos [?]: 4200 [0]
Given Kudos: 160
Location: India
GMAT 1: 690 Q50 V34
WE:Engineering (Transportation)
Re: If x = -1, then -(x^4 + x^3 + x^2 + x) = [#permalink]
Bunuel wrote:
The Official Guide For GMAT® Quantitative Review, 2ND Edition

If x = -1, then -(x^4 + x^3 + x^2 + x) =

(A) -10
(B) - 4
(C) 0
(D) 4
(E) 10

Problem Solving
Question: 74
Category: Arithmetic Operations on rational numbers
Page: 71
Difficulty: 550

GMAT Club is introducing a new project: The Official Guide For GMAT® Quantitative Review, 2ND Edition - Quantitative Questions Project

Each week we'll be posting several questions from The Official Guide For GMAT® Quantitative Review, 2ND Edition and then after couple of days we'll provide Official Answer (OA) to them along with a slution.

We'll be glad if you participate in development of this project:
1. Please provide your solutions to the questions;
2. Please vote for the best solutions by pressing Kudos button;
3. Please vote for the questions themselves by pressing Kudos button;
4. Please share your views on difficulty level of the questions, so that we have most precise evaluation.

Thank you!

Given: x = -1

Asked: -(x^4 + x^3 + x^2 + x) = ?

-(x^4 + x^3 + x^2 + x) = - (1-1+1-1) = 0

IMO C
Re: If x = -1, then -(x^4 + x^3 + x^2 + x) = [#permalink]
Moderator:
Math Expert
94370 posts